Contribution to vector control by essential oils of Aucoumea klaineana, Canarium schweinfurthii, Cymbopogon nardus, Dacryodes edulis and Eucalyptus citriodora from Gabon - Cédric Sima Obiang; Thiery Ndong Mba; Rick-Léonid Ngoua Meye Misso; Juliette Ornely Orango Bourdette; Guy Roger Ndong Atome; Joseph Privat Ondo; Louis-Clément Obame Engonga (Shahrekord University of Medical Sciences, 2022)
Introduction: Aucoumea klaineana, Canarium schweinfurthii, Cymbopogon nardus, Dacryodes edulis, and Eucalyptus citriodora are of Gabonese origin, believed to have insecticidal activity. This study contributes to vector control by the insecticidal activities (larvicidal and ovicidal) of five essential oils from these plants against Anopheles gambiae, a major vector of malaria in Gabon. Methods: The essential oils were extracted by hydrodistillation. Larvicidal and ovicidal effects of essential oils were performed using different concentrations on third and fourth instar larvae and eggs of A. gambiae vectors. The effects of these oils were examined on the mortality rate of larvae and eggs. Results: The essential oils of A. klaineana, C. schweinfurthii, C. nardus, A. edulis, and E. citriodora showed greater activity against mosquito larvae (7.33 < LC50 < 107.14) compared to eggs (22.80 < LC50 < 64.63). D. edulis showed the highest activity against Anopheles gambiae eggs and larvae. Of all plants, essential oils from A. klaineana showed the lowest activity of A. gambiae eggs and larvae. Larvae were more sensitive than eggs. All essential oils were toxic to the various aquatic vectors of malaria. Conclusion: The study reveals the potential ovicidal efficacy and larvicidal activity of these plants against A. gambiae.